Healthcare Professionals’ Identification of, and Solutions to, Health Problems for Hard to Reach Patients with Diabetes - Ørsted, Anette Stamer; Nissen, Maria Appel; Vardinghus-Nielsen, Henrik (Professions and professionalism, 2025)
This article examines how healthcare professionals understand children with type 1 diabetes and their families, and how they consider them hard to reach. Based on observations and analysis of healthcare professionals’ case conferences, the article finds that families’ lack of compliance with professional recommendations is explained by parental lack of resources, ability, willingness, and complex social and personal problems of the family members. To find solutions to these diabetes management problems, the professionals integrate and synthesize knowledge based on experience, judgment, and practical skills. They also recognize organizational limitations of the healthcare system and, consequently, dependency on other organizations with other functions and knowledge. The article contributes to new knowledge about how organizations and professionals try to address and solve problems of health inequality in practice. A major finding is that the capacity to address individual health literacy depends just as much on organizational health literacy.